Anticorrosive-flame-retardant alkyd primer and preparation method thereof

CN119529644BActive Publication Date: 2026-10-30JIANGSU LUPU RESOURCES UTILIZATION & DEV CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411773274.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2026-10-30
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

[0004]有鉴于此,本发明的目的在于提出一种防腐-阻燃醇酸底漆及其制备方法,以解决现有技术不能大规模、高附加值的利用富磷高锰钢渣粉、富磷高锰钢渣或一般钢渣具有强碱性,会导致醇酸树脂快速凝结的问题

Benefits of technology

[0028]1、本发明解决了现有技术不能大规模、高附加值的利用富磷高锰钢渣粉;一般钢渣中P2O5或MnO含量低,其加工后具有一定防腐性,不具有阻燃性(非耐高温性);常规防腐填料多为铁红粉,目前铁红粉逐渐成为新能源电池的主要原料,导致用于防腐填料的铁红粉产量少、价格高;利用磷酸或磷酸盐与一般钢渣进行复合,虽然也可以形成Si-P-Al、Si-P-Mg和Si-P-Fe体系,但是磷酸会腐蚀加工设备,磷酸盐生产能耗高不满足政策目标;富磷高锰钢渣或一般钢渣具有强碱性,会导致醇酸树脂快速凝结的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of solid waste resource utilization, and particularly relates to a corrosion-resistant and flame-retardant alkyd primer and a preparation method thereof. The present application solves the problem that the prior art cannot utilize phosphorus-rich high-manganese steel slag powder on a large scale and with high added value. The P2O5 or MnO content in general steel slag is low, and the steel slag has certain corrosion resistance after processing but does not have flame retardance (non-high-temperature resistance). The conventional corrosion-resistant filler is mostly iron red powder, and at present, the iron red powder gradually becomes the main raw material of new energy batteries, resulting in a small output and high price of the iron red powder used as the corrosion-resistant filler. The phosphorus-rich high-manganese steel slag or general steel slag has strong alkalinity, which can cause the problem of rapid coagulation of alkyd resin. The solution to the above problems not only reduces the production cost of the existing single-component alkyd primer, but also realizes the corrosion-resistant and flame-retardant integration of the single-component alkyd primer, and fully utilizes the phosphorus-rich high-manganese steel slag powder to achieve the high added value and carbon reduction targets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste resource utilization technology, and in particular to an anti-corrosion and flame-retardant alkyd primer and its preparation method. Background Technology

[0002] Phosphorus-rich, high-manganese steel slag is a solid waste generated during steelmaking, containing high levels of MnO (4.588%-6.107%) and P2O5 (2.604%-3.315%). Currently, the large-scale stockpiling of phosphorus-rich, high-manganese steel slag not only occupies valuable land but also pollutes the surrounding environment and groundwater. Therefore, how to utilize phosphorus-rich, high-manganese steel slag on a large scale with high added value to reduce environmental burden and increase enterprise efficiency is an urgent problem that needs to be solved.

[0003] In coatings, anti-corrosion pigments and fillers primarily enhance the corrosion resistance of anti-corrosion coatings, thereby extending their service life. Currently, the main anti-corrosion pigments and fillers in coatings include iron oxide, mica iron oxide, chromium oxide, and zinc oxide. However, these pigments and fillers all contain large amounts of heavy metal oxides such as chromium, zinc, and lead, which enter the coating along with the pigments and fillers during use, leading to serious environmental pollution problems. To address these issues, phosphorus-rich high-manganese steel slag, containing high levels of CaO, Fe2O3, SiO2, MgO, MnO, Al2O3, and P2O5, can be processed into phosphorus-rich high-manganese steel slag powder. This powder can be used as a functional filler to replace iron oxide red powder, phosphoric acid, or phosphates in general steel slag for use in single-component alkyd primers. The aim is to achieve high-value-added recycling of phosphorus-rich high-manganese steel slag powder, and to meet the multifunctionality and carbon reduction requirements of single-component alkyd primers. Summary of the Invention

[0004] In view of this, the purpose of this invention is to propose an anti-corrosion and flame-retardant alkyd primer and its preparation method, to solve the problem that existing technologies cannot utilize phosphorus-rich high-manganese steel slag powder on a large scale and with high added value, and that the strong alkalinity of phosphorus-rich high-manganese steel slag or ordinary steel slag leads to rapid coagulation of alkyd resin. This invention utilizes phosphorus-rich high-manganese steel slag, which, through ultrafine grinding, forms phosphorus-rich high-manganese steel slag powder. On the one hand, due to its high specific surface area, it replaces iron oxide powder, phosphoric acid, or phosphates in the action of ordinary steel slag. On the other hand, through the action of modified resin, it solves the problem of high alkyd resin coagulation caused by the high alkalinity of phosphorus-rich high-manganese steel slag. For the first time, this invention achieves synergistic anti-corrosion and flame-retardant properties in a single-component alkyd primer, preparing a low-carbon single-component anti-corrosion and flame-retardant alkyd primer based on phosphorus-rich high-manganese steel slag powder. Simultaneously, the stirring speed and stirring time are controlled to achieve high-value-added recycling of phosphorus-rich high-manganese steel slag powder.

[0005] To achieve the above objectives, the present invention provides an anti-corrosion and flame-retardant alkyd primer, wherein the alkyd primer comprises the following raw materials by weight percentage:

[0006]

[0007] The chemical composition of the phosphorus-rich high-manganese steel slag powder is as follows: CaO 33.927%-36.704%, Fe2O3 26.711%-29.935%, SiO2 13.578%-15.792%, MgO 4.588%-8.910%, MnO 4.588%-6.107%, Al2O3 1.994%-3.621%, P2O5 2.604%-3.315%, and other impurities 2.474%-3.389%; the ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the chemical composition mass percentages of CaO, MgO, and SiO2, respectively, and R ≤ 3.30.

[0008] The additives include 0.3%–0.6% wetting and dispersing agent, 1.0%–1.5% dust suppressant, 0.2%–0.5% leveling agent, 0.1%–0.3% defoamer, and 0.1%–0.3% drying agent.

[0009] The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent; the dust suppressant is 410 type dust suppressant; the leveling agent is XYS-5313 type leveling agent; the defoamer is XYS-6550 type defoamer; and the drying agent is an oil-based drying agent.

[0010] The weak acid-based ethanol modifier is a mixture of a weak acid and ethanol, with a mass ratio of weak acid to ethanol of 4:1, wherein the weak acid is one of phosphoric acid, formic acid, or acetic acid.

[0011] The silane coupling agent is one of KH-550, KH-560 or KH-570.

[0012] The alkyd resin is a dry alkyd resin.

[0013] The modified resin is a cation exchange resin.

[0014] The xylene is of industrial grade.

[0015] The bentonite is either calcium-based bentonite or sodium-based bentonite.

[0016] The fineness of the phosphorus-rich high-manganese steel slag powder is 800-1000 mesh, the fineness of the bentonite is 800-1000 mesh, and the fineness of the talc powder is 1000-1250 mesh.

[0017] The present invention also provides a method for preparing the anti-corrosion and flame-retardant alkyd primer, comprising the following steps:

[0018] S1. Mix phosphorus-rich high-manganese steel slag powder with weak acid-based ethanol modifier according to the formula. The mixing temperature is 60-70℃, the mixing speed is 300-500r / min, and the mixing time is 60-120min to obtain weak acid-based ethanol modified phosphorus-rich high-manganese steel slag powder.

[0019] S2. The weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with the formulated amount of silane coupling agent. The stirring temperature is 75-85℃, the stirring speed is 300-500r / min, and the stirring time is 60-120min to obtain silane coupling-weak acid ethanol modified phosphorus-rich high manganese steel slag powder.

[0020] S3. The silane-coupled-weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with the formulated amount of alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The mixing speed is 400-600 r / min and the mixing time is 180-240 min to obtain the anti-corrosion-flame retardant alkyd primer precursor.

[0021] S4. Mix the anti-corrosion and flame-retardant alkyd primer precursor with the formulated amount of drying agent at a stirring speed of 600-800 r / min and a stirring time of 60-90 min to obtain the anti-corrosion and flame-retardant alkyd primer.

[0022] The scientific principle of this invention:

[0023] (1) The phosphorus-rich high manganese steel slag powder contains Fe2O3, which has anti-corrosion properties and can replace expensive iron oxide powder as an anti-corrosion pigment and filler for primer. On the other hand, it contains CaO and SiO2, which can form a silicate system and have surface covering properties, which can isolate external corrosive substances from eroding the primer coating. At the same time, it contains MnO, which has good wear resistance, which can promote the wear resistance of the primer coating and indirectly enhance the resistance to external corrosive substances from eroding the primer coating.

[0024] (2) The P2O5 content in phosphorus-rich high-manganese steel slag powder is 2.604%-3.315%, which is higher than that of ordinary steel slag. Therefore, during the combustion process of the primer coating, it can form Si-P-Al, Si-P-Mg flame retardant systems and Si-P-Fe smoke suppression and toxicity reduction systems with SiO2, MgO, Al2O3, and Fe2O3 in the phosphorus-rich high-manganese steel slag powder, thereby achieving a flame retardant effect. At the same time, the formation of a dense carbon layer effectively blocks the transfer of combustible gases, oxygen, and heat. The iron ions contained in the phosphorus-rich high-manganese steel slag powder, through the oxidation-reduction cycle, catalyze the combustible gases such as CO produced during combustion to form non-toxic CO2, thereby achieving smoke suppression and toxicity reduction.

[0025] (3) The fineness of phosphorus-rich high manganese steel slag powder is 800-1000 mesh, and its specific surface area is large. This not only increases the contact area with the alkyd system and improves the various properties of the coating, but also, during the combustion process, the metal elements in the phosphorus-rich high manganese steel slag powder, on the one hand, Si, P, Al, Mg and Fe elements construct Si-P-Al, Si-P-Mg flame retardant systems and Si-P-Fe smoke suppression and toxicity reduction systems, and on the other hand, Mn elements catalyze combustible products such as hydrocarbons to remain in the condensed phase to form a carbon layer.

[0026] (4) The CaO content in phosphorus-rich high-manganese steel slag powder is relatively high at 33.927%-36.704%, which makes the alkyd resin very easy to coagulate. Therefore, it is necessary to control the ternary basicity R in phosphorus-rich high-manganese steel slag powder, and then use the ions in the modified resin of cation exchange resin to suppress the alkalinity of phosphorus-rich high-manganese steel slag powder, thereby greatly improving the compatibility of the alkyd system and the stability of the coating film.

[0027] The beneficial effects of this invention are:

[0028] 1. This invention solves the problem that existing technologies cannot utilize phosphorus-rich high-manganese steel slag powder on a large scale and with high added value. General steel slag has low P2O5 or MnO content, and while it has some corrosion resistance after processing, it lacks flame retardancy (and high-temperature resistance). Conventional anti-corrosion fillers are mostly iron oxide powder, which is gradually becoming a major raw material for new energy batteries, resulting in low production and high prices for iron oxide powder used as an anti-corrosion filler. While compounding phosphoric acid or phosphates with general steel slag can form Si-P-Al, Si-P-Mg, and Si-P-Fe systems, phosphoric acid corrodes processing equipment, and phosphate production has high energy consumption, failing to meet policy objectives. Furthermore, phosphorus-rich high-manganese steel slag or general steel slag is highly alkaline, leading to rapid coagulation of alkyd resins.

[0029] 2. This invention utilizes phosphorus-rich, high-manganese steel slag, which is ultrafine ground to form phosphorus-rich, high-manganese steel slag powder. On one hand, due to its high specific surface area, it replaces iron oxide powder, phosphoric acid, or phosphates in the action of ordinary steel slag. On the other hand, through the action of modified resin, it solves the problem of high alkyd resin coagulation caused by the high alkyd resin's high alkyd content. For the first time, it achieves synergistic anti-corrosion and flame-retardant properties in a single-component alkyd primer, preparing a low-carbon, single-component anti-corrosion and flame-retardant alkyd primer based on phosphorus-rich, high-manganese steel slag powder. Simultaneously, it controls the stirring speed and time to achieve high-value-added recycling of phosphorus-rich, high-manganese steel slag powder, as well as the multifunctionality and carbon reduction target of the single-component alkyd primer.

[0030] 3. The anti-corrosion and flame-retardant alkyd primer and its preparation method of the present invention meet the relevant policy requirements for energy conservation, environmental protection and circular economy. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0032] It should be noted that, unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0033] Example 1

[0034] Taking the preparation of 100g of the product in this embodiment as an example, the components and their mass ratios are as follows:

[0035]

[0036] The phosphorus-rich high-manganese steel slag powder has a fineness of 800 mesh, and its chemical composition by mass percentage is: CaO 35.281%, Fe2O3 27.000%, SiO2 15.792%, MgO 8.616%, MnO 6.107%, Al2O3 1.994%, P2O5 2.736%, and others 2.474%. The ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R = 2.78. The weak acid-based ethanol modifier is a mixture of phosphoric acid and ethanol, with a phosphoric acid concentration of 80% and an ethanol concentration of 95%, and a phosphoric acid to ethanol mass ratio of 4:1. The silane coupling agent is KH-570. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is calcium-based bentonite with a fineness of 900 mesh. The talc powder has a fineness of 1250 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is 410 type dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is 16% oil-based drying agent.

[0037] (1) Using a constant temperature magnetic stirrer, phosphorus-rich high manganese steel slag powder was mixed with a weak acid-based ethanol modifier. The stirring temperature was 70℃, the stirring speed was 300r / min, and the stirring time was 90min to obtain weak acid-based ethanol modified phosphorus-rich high manganese steel slag powder.

[0038] (2) The weak acid ethanol modified phosphorus-rich high manganese steel slag powder was mixed with silane coupling agent using a constant temperature magnetic stirrer. The stirring temperature was 75℃, the stirring speed was 400r / min, and the stirring time was 60min to obtain silane coupling-weak acid ethanol modified phosphorus-rich high manganese steel slag powder.

[0039] (3) Using a magnetic stirrer, the silane-coupled-weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 500 r / min and the stirring time is 240 min to obtain a low carbon single component anti-corrosion-flame retardant alkyd primer precursor based on phosphorus-rich high manganese steel slag powder.

[0040] (4) Use a magnetic stirrer to mix the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 600 r / min and the stirring time is 60 min to obtain the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0041] Example 2

[0042] Taking the preparation of 100g of the product in this embodiment as an example, the components and their mass ratios are as follows:

[0043]

[0044]

[0045] The phosphorus-rich high-manganese steel slag powder has a fineness of 1000 mesh, and its chemical composition by mass percentage is: CaO 34.476%, Fe2O3 27.039%, SiO2 14.897%, MgO 8.421%, MnO 5.644%, Al2O3 3.328%, P2O5 3.315%, and others 2.880%. The ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R = 2.88. The weak acid-based ethanol modifier is a mixture of acetic acid and ethanol, with a mass ratio of acetic acid to ethanol of 4:1. The silane coupling agent is KH-560. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weak acid cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 800 mesh. The talc powder has a fineness of 1000 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is 410 type dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is 16% oil-based drying agent.

[0046] (1) Using a constant temperature magnetic stirrer, phosphorus-rich high-manganese steel slag powder was mixed with a weak acid-based ethanol modifier. The stirring temperature was 60℃, the stirring speed was 400r / min, and the stirring time was 120min to obtain weak acid-based ethanol modified phosphorus-rich high-manganese steel slag powder.

[0047] (2) The weak acid ethanol modified phosphorus-rich high manganese steel slag powder was mixed with silane coupling agent using a constant temperature magnetic stirrer. The stirring temperature was 80℃, the stirring speed was 500r / min, and the stirring time was 90min to obtain silane coupling-weak acid ethanol modified phosphorus-rich high manganese steel slag powder.

[0048] (3) Using a magnetic stirrer, the silane-coupled-weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 600 r / min and the stirring time is 180 min to obtain a low carbon single component anti-corrosion-flame retardant alkyd primer precursor based on phosphorus-rich high manganese steel slag powder.

[0049] (4) Use a magnetic stirrer to mix the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 700 r / min and the stirring time is 90 min to obtain the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0050] Example 3

[0051] Taking the preparation of 100g of the product in this embodiment as an example, the components and their mass ratios are as follows:

[0052]

[0053] The phosphorus-rich high-manganese steel slag powder has a fineness of 900 mesh, and its chemical composition by mass percentage is: CaO 36.298%, Fe2O3 28.035%, SiO2 14.186%, MgO 7.455%, MnO 5.186%, Al2O3 2.629%, P2O5 3.121%, and others 3.090%. The ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R = 3.08. The weak acid-based ethanol modifier is a mixture of formic acid and ethanol, with an ethanol concentration of 95% and a formic acid to ethanol mass ratio of 4:1. The silane coupling agent is KH-550. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weak acid cation exchange resin. The xylene is industrial grade. The bentonite is calcium-based bentonite with a fineness of 1000 mesh. The talc powder has a fineness of 1100 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is type 410 dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is 16% oil-based drying agent.

[0054] (1) Using a constant temperature magnetic stirrer, phosphorus-rich high-manganese steel slag powder was mixed with a weak acid-based ethanol modifier. The stirring temperature was 65℃, the stirring speed was 500r / min, and the stirring time was 60min to obtain weak acid-based ethanol modified phosphorus-rich high-manganese steel slag powder.

[0055] (2) The weak acid ethanol modified phosphorus-rich high manganese steel slag powder was mixed with silane coupling agent using a constant temperature magnetic stirrer. The stirring temperature was 85℃, the stirring speed was 300r / min, and the stirring time was 120min to obtain silane coupling-weak acid ethanol modified phosphorus-rich high manganese steel slag powder.

[0056] (3) Using a magnetic stirrer, the silane-coupled-weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 400 r / min and the stirring time is 210 min to obtain a low carbon single component anti-corrosion-flame retardant alkyd primer precursor based on phosphorus-rich high manganese steel slag powder.

[0057] (4) Use a magnetic stirrer to mix the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 800 r / min and the stirring time is 75 min to obtain the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0058] Example 4

[0059] Taking the preparation of 100g of the product in this embodiment as an example, the components and their mass ratios are as follows:

[0060]

[0061] The phosphorus-rich high-manganese steel slag powder has a fineness of 800 mesh, and its chemical composition by mass percentage is: CaO 36.704%, Fe2O3 26.711%, SiO2 14.650%, MgO 6.949%, MnO 4.588%, Al2O3 3.621%, P2O5 3.388%, and others 3.389%. The ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R = 2.98. The weak acid-based ethanol modifier is a mixture of acetic acid and ethanol, with an ethanol concentration of 95% and an acetic acid to ethanol mass ratio of 4:1. The silane coupling agent is KH-570. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weak acid cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 1000 mesh. The talc powder has a fineness of 1200 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is 410 type dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is 16% oil-based drying agent.

[0062] (1) Using a constant temperature magnetic stirrer, phosphorus-rich high-manganese steel slag powder was mixed with a weak acid-based ethanol modifier. The stirring temperature was 60℃, the stirring speed was 300r / min, and the stirring time was 90min to obtain weak acid-based ethanol modified phosphorus-rich high-manganese steel slag powder.

[0063] (2) The weak acid ethanol modified phosphorus-rich high manganese steel slag powder was mixed with silane coupling agent using a constant temperature magnetic stirrer. The stirring temperature was 85℃, the stirring speed was 300r / min, and the stirring time was 90min to obtain silane coupling-weak acid ethanol modified phosphorus-rich high manganese steel slag powder.

[0064] (3) Using a magnetic stirrer, the silane-coupled-weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 400 r / min and the stirring time is 180 min to obtain a low carbon single component anti-corrosion-flame retardant alkyd primer precursor based on phosphorus-rich high manganese steel slag powder.

[0065] (4) Use a magnetic stirrer to mix the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 700 r / min and the stirring time is 60 min to obtain the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0066] Example 5

[0067] Taking the preparation of 100g of the product in this embodiment as an example, the components and their mass ratios are as follows:

[0068]

[0069]

[0070] The phosphorus-rich high-manganese steel slag powder has a fineness of 1000 mesh, and its chemical composition by mass percentage is: CaO 33.927%, Fe2O3 29.935%, SiO2 13.785%, MgO 8.609%, MnO 5.213%, Al2O3 2.726%, P2O5 2.604%, and others 3.201%. The ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R = 3.09. The weak acid-based ethanol modifier is a mixture of phosphoric acid and ethanol, with a phosphoric acid concentration of 80% and an ethanol concentration of 95%, and a phosphoric acid to ethanol mass ratio of 4:1. The silane coupling agent is KH-550. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is calcium-based bentonite with a fineness of 800 mesh. The talc powder has a fineness of 1050 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is 410 type dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is 16% oil-based drying agent.

[0071] (1) Using a constant temperature magnetic stirrer, phosphorus-rich high-manganese steel slag powder was mixed with a weak acid-based ethanol modifier. The stirring temperature was 70℃, the stirring speed was 500r / min, and the stirring time was 120min to obtain weak acid-based ethanol modified phosphorus-rich high-manganese steel slag powder.

[0072] (2) The weak acid ethanol modified phosphorus-rich high manganese steel slag powder was mixed with silane coupling agent using a constant temperature magnetic stirrer. The stirring temperature was 75℃, the stirring speed was 500r / min, and the stirring time was 60min to obtain silane coupling-weak acid ethanol modified phosphorus-rich high manganese steel slag powder.

[0073] (3) Using a magnetic stirrer, the silane-coupled-weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 600 r / min and the stirring time is 210 min to obtain a low carbon single component anti-corrosion-flame retardant alkyd primer precursor based on phosphorus-rich high manganese steel slag powder.

[0074] (4) Use a magnetic stirrer to mix the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 600 r / min and the stirring time is 90 min to obtain the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0075] Example 6

[0076] Taking the preparation of 100g of the product in this embodiment as an example, the components and their mass ratios are as follows:

[0077]

[0078]

[0079] The phosphorus-rich high-manganese steel slag powder has a fineness of 900 mesh, and its chemical composition by mass percentage is: CaO 35.284%, Fe2O3 27.581%, SiO2 13.578%, MgO 8.910%, MnO 5.471%, Al2O3 3.309%, P2O5 2.615%, and others 3.252%. The ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R = 3.25. The weak acid-based ethanol modifier is a mixture of formic acid and ethanol, with an ethanol concentration of 95% and a formic acid to ethanol mass ratio of 4:1. The silane coupling agent is KH-560. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weak acid cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 900 mesh. The talc powder has a fineness of 1150 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is type 410 dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is 16% oil-based drying agent.

[0080] (1) Using a constant temperature magnetic stirrer, phosphorus-rich high-manganese steel slag powder was mixed with a weak acid-based ethanol modifier. The stirring temperature was 65℃, the stirring speed was 400r / min, and the stirring time was 60min to obtain weak acid-based ethanol modified phosphorus-rich high-manganese steel slag powder.

[0081] (2) The weak acid ethanol modified phosphorus-rich high manganese steel slag powder was mixed with silane coupling agent using a constant temperature magnetic stirrer. The stirring temperature was 80℃, the stirring speed was 400r / min, and the stirring time was 120min to obtain silane coupling-weak acid ethanol modified phosphorus-rich high manganese steel slag powder.

[0082] (3) Using a magnetic stirrer, the silane-coupled-weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 500 r / min and the stirring time is 240 min to obtain a low carbon single component anti-corrosion-flame retardant alkyd primer precursor based on phosphorus-rich high manganese steel slag powder.

[0083] (4) Use a magnetic stirrer to mix the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 800 r / min and the stirring time is 75 min to obtain the phosphorus-rich high manganese steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0084] Comparative Example 1

[0085] Taking the preparation of 100g of this comparative product as an example, the components and their mass ratios are as follows:

[0086]

[0087] The general steel slag powder has a fineness of 900 mesh, and its chemical composition by mass percentage is: CaO 49.900%, Fe2O3 24.520%, SiO2 11.670%, MgO 3.940%, MnO 2.130%, Al2O3 2.900%, P2O5 2.540%, and others 2.400% (refer to "A steel slag PVC calendering film matrix material and its preparation method", ZL202210608582.6); the ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R = 4.61. The weak acid-based ethanol modifier is a mixture of weak acid and ethanol, with a mass ratio of weak acid to ethanol of 4:1, wherein the weak acid is formic acid. The silane coupling agent is KH-560. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 900 mesh. The talc powder has a fineness of 1150 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is type 410 dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is a 16% oil-based drying agent.

[0088] (1) Use a constant temperature magnetic stirrer to mix general steel slag powder with weak acid ethanol modifier. The stirring temperature is 65℃, the stirring speed is 400r / min, and the stirring time is 60min to obtain weak acid ethanol modified general steel slag powder.

[0089] (2) Use a constant temperature magnetic stirrer to mix general steel slag powder modified with weak acid ethanol and silane coupling agent. The stirring temperature is 80℃, the stirring speed is 400r / min and the stirring time is 120min to obtain silane coupling-weak acid ethanol modified general steel slag powder.

[0090] (3) Using a magnetic stirrer, silane-coupled-weak acid ethanol modified general steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 500 r / min and the stirring time is 240 min to obtain general steel slag powder-based low carbon single component anti-corrosion and flame retardant alkyd primer precursor.

[0091] (4) Use a magnetic stirrer to mix the general steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 800 r / min and the stirring time is 75 min to obtain the general steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0092] Comparative Example 2

[0093] Taking the preparation of 100g of this comparative product as an example, the components and their mass ratios are as follows:

[0094]

[0095]

[0096] The general steel slag powder has a fineness of 900 mesh, and its chemical composition by mass percentage is: CaO 38.940%, Fe2O3 33.140%, SiO2 11.140%, MgO 3.400%, MnO 3.490%, Al2O3 2.790%, P2O5 0.190%, and others 6.910% (refer to "A Modified Porous Steel Slag for Rubber Filler and Its Preparation Method", ZL201710201458.7); the ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R = 3.80. The weak acid-based ethanol modifier is a mixture of a weak acid and ethanol, with a mass ratio of 4:1, wherein the weak acid is formic acid. The silane coupling agent is KH-560. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weakly acidic cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 900 mesh. The talc powder has a fineness of 1150 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is type 410 dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is a 16% oil-based drying agent.

[0097] (1) Use a constant temperature magnetic stirrer to mix general steel slag powder with weak acid ethanol modifier. The stirring temperature is 65℃, the stirring speed is 400r / min, and the stirring time is 60min to obtain weak acid ethanol modified general steel slag powder.

[0098] (2) Use a constant temperature magnetic stirrer to mix general steel slag powder modified with weak acid ethanol and silane coupling agent. The stirring temperature is 80℃, the stirring speed is 400r / min and the stirring time is 120min to obtain silane coupling-weak acid ethanol modified general steel slag powder.

[0099] (3) Using a magnetic stirrer, silane-coupled-weak acid ethanol modified general steel slag powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 500 r / min and the stirring time is 240 min to obtain general steel slag powder-based low carbon single component anti-corrosion and flame retardant alkyd primer precursor.

[0100] (4) Use a magnetic stirrer to mix the general steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 800 r / min and the stirring time is 75 min to obtain the general steel slag powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0101] Comparative Example 3

[0102] Taking the preparation of 100g of this comparative product as an example, the components and their mass ratios are as follows:

[0103]

[0104]

[0105] The iron oxide red powder has a fineness of 900 mesh. The weak acid-based ethanol modifier is a mixture of weak acid and ethanol, with a mass ratio of weak acid to ethanol of 4:1, wherein the weak acid is formic acid. The silane coupling agent is KH-560. The alkyd resin is a dry, medium-oil alkyd resin. The modified resin is a weak acid cation exchange resin. The xylene is industrial grade. The bentonite is sodium-based bentonite with a fineness of 900 mesh. The talc powder has a fineness of 1150 mesh. The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent. The dust suppressant is 410 type dust suppressant. The leveling agent is XYS-5313 type leveling agent. The defoamer is XYS-6550 type defoamer. The drying agent is a 16% oil-based drying agent.

[0106] (1) Iron oxide powder and weak acid ethanol modifier were mixed using a constant temperature magnetic stirrer at a stirring temperature of 65℃, a stirring speed of 400r / min and a stirring time of 60min to obtain iron oxide powder modified with weak acid ethanol.

[0107] (2) The weak acid ethanol modified iron oxide powder and the silane coupling agent were mixed using a constant temperature magnetic stirrer. The stirring temperature was 80℃, the stirring speed was 400r / min, and the stirring time was 120min to obtain silane coupling-weak acid ethanol modified iron oxide powder.

[0108] (3) Using a magnetic stirrer, silane-coupled weak acid ethanol modified iron oxide powder is mixed with alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The stirring speed is 500 r / min and the stirring time is 240 min to obtain iron oxide powder-based low carbon single component anti-corrosion and flame retardant alkyd primer precursor.

[0109] (4) Use a magnetic stirrer to mix the iron oxide red powder-based low carbon single component anti-corrosion-flame retardant alkyd primer precursor with a drying agent. The stirring speed is 800 r / min and the stirring time is 75 min to obtain the iron oxide red powder-based low carbon single component anti-corrosion-flame retardant alkyd primer.

[0110] The performance test results of Preparation Examples 1-6 and Comparative Examples 1-3 are shown in Table 1 below:

[0111] Table 1 Performance of Phosphorus-Rich High-Manganese Steel Slag Powder-Based Low-Carbon Single-Component Anti-Corrosion and Flame-Retardant Alkyd Primer

[0112]

[0113] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity. Any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the invention should be included within the scope of protection of the invention.

Claims

1. A corrosion-resistant and flame-retardant alkyd primer, characterized in that, The alkyd primer comprises the following raw materials by weight percentage: 20%–25% phosphorus-rich, high-manganese steel slag powder Weak acid ethanol modifier 0.5%–0.8% Silane coupling agent 0.4%–0.6% Alkyd resin 33%–44% Modified resin 2%–5% Xylene 23%–27% Bentonite 0.3%–0.6% Talc powder 8%–12% Additives: 1.7%–3.2%; The chemical composition of the phosphorus-rich high-manganese steel slag powder, by mass percentage, is as follows: CaO 33.927%-36.704%, Fe2O3 26.711%-29.935%, SiO2 13.578%-15.792%, MgO 4.588%-8.910%, MnO 4.588%-6.107%, Al2O3 1.994%-3.621%, and P2O5 2.604%-3.315%. Other impurities range from 2.474% to 3.389%; the ternary basicity R = (MCaO + MMgO) / MSiO2, where MCaO, MMgO, and MSiO2 correspond to the mass percentages of CaO, MgO, and SiO2, respectively, and R ≤ 3.30; the modified resin is a cation exchange resin, and the weak acid-based ethanol modifier is a mixture of a weak acid and ethanol, with a mass ratio of 4:1 between the weak acid and ethanol, wherein the weak acid is one of phosphoric acid, formic acid, or acetic acid.

2. The anti-corrosion and flame-retardant alkyd primer according to claim 1, characterized in that, The additives include 0.3%–0.6% wetting and dispersing agent, 1.0%–1.5% dust suppressant, 0.2%–0.5% leveling agent, 0.1%–0.3% defoamer, and 0.1%–0.3% drying agent.

3. The anti-corrosion and flame-retardant alkyd primer according to claim 2, characterized in that, The wetting and dispersing agent is XYS-6800 type wetting and dispersing agent; the dust suppressant is 410 type dust suppressant; the leveling agent is XYS-5313 type leveling agent; the defoamer is XYS-6550 type defoamer; and the drying agent is an oil-based drying agent.

4. The anti-corrosion and flame-retardant alkyd primer according to claim 2, characterized in that, The silane coupling agent is one of KH-550, KH-560 or KH-570.

5. The anti-corrosion and flame-retardant alkyd primer according to claim 2, characterized in that, The alkyd resin is a dry alkyd resin.

6. The anti-corrosion and flame-retardant alkyd primer according to claim 2, characterized in that, The bentonite is either calcium-based bentonite or sodium-based bentonite.

7. The anti-corrosion and flame-retardant alkyd primer according to claim 2, characterized in that, The fineness of the phosphorus-rich high-manganese steel slag powder is 800-1000 mesh, the fineness of the bentonite is 800-1000 mesh, and the fineness of the talc powder is 1000-1250 mesh.

8. The method for preparing the anti-corrosion and flame-retardant alkyd primer according to any one of claims 2-7, characterized in that, Includes the following steps: S1. Mix phosphorus-rich high-manganese steel slag powder with weak acid-based ethanol modifier according to the formula. The mixing temperature is 60-70℃, the mixing speed is 300-500r / min, and the mixing time is 60-120min to obtain weak acid-based ethanol modified phosphorus-rich high-manganese steel slag powder. S2. The weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with the formulated amount of silane coupling agent. The stirring temperature is 75-85℃, the stirring speed is 300-500r / min, and the stirring time is 60-120min to obtain silane coupling-weak acid ethanol modified phosphorus-rich high manganese steel slag powder. S3. The silane-coupled-weak acid ethanol modified phosphorus-rich high manganese steel slag powder is mixed with the formulated amount of alkyd resin, modified resin, xylene, bentonite, talc, wetting and dispersing agent, dust suppressant, leveling agent and defoamer. The mixing speed is 400-600 r / min and the mixing time is 180-240 min to obtain the anti-corrosion-flame retardant alkyd primer precursor. S4. Mix the anti-corrosion and flame-retardant alkyd primer precursor with the formulated amount of drying agent at a stirring speed of 600-800 r / min and a stirring time of 60-90 min to obtain the anti-corrosion and flame-retardant alkyd primer.

Citation Information

Patent Citations

  • Modified porous steel slag for rubber filler and preparation method thereof

    CN106893139A

  • A steel slag PVC calendered film matrix material and its preparation method

    CN114773752B

  • Solid waste resource utilization type antirust-flame-retardant-physique integrated pigment and filler and preparation method thereof

    CN110616003A

  • High-free calcium oxide solid waste-based cementing material as well as preparation and application thereof

    CN113831036A